The Use of Rap to Combat Linguistic Racism: a Didactic Sequence for Teaching Portuguese Language: a Didactic Sequence for Teaching Portuguese Language - Laurindo Batista, Eliane; Pereira Caetano, Joane Marieli (Revista Letras Raras, 2024)
In this work, based on the discussion about how to intervene in the impact of linguistic racism through the teaching of Portuguese, we intend to propose a Didactic Sequence, using the Rap genre, whose Modules will encourage an anti-racist pedagogical practice. Specifically, the aim is to understand linguistic racism and analyze its modus operandi in Brazil; to analyze the recognition of the Afro-Brazilian vernacular, also known as pretuguese, and its flagrant absence in educational practices and, finally, to propose a methodological suggestion to combat linguistic racism. Methodologically, this is a qualitative study. Firstly, a bibliographical review was carried out with the theoretical support of Silva (2004) on the history of the Portuguese language; Nascimento (2019), Gonzalez (1983) (1988), who address the relationship between race and language; Souza (2011) analyzed the didactic contributions for working with the genre chosen for this proposal, rap; with a view to preparing the didactic sequence, it was based on the authors Dolz, Noverraz and Schneuwly (2004). In the second stage, a methodological suggestion for a Didactic Sequence with the rap genre is presented, focusing the discussion on linguistic racism. The results showed the existence of Linguistic Racism, in that it highlighted how certain linguistic variants of non-white origin are stigmatized and devalued. The study also recognized the transformative potential of Rap as a decolonizing tool to overcome Portuguese language teaching based on the Eurocentric model.